(untitled) (International Educators Conference, 2025)
This article analyzes the artistic and philosophical interpretation of the image of the dog in 20th-century literature and its semantic evolution related to society, human psychology, and cultural values. The transformation of the dog image in literature is primarily explained by the reconsideration of the social and moral boundaries between humans and animals. The 20th century, characterized by wars, technological progress, and the crisis of human values, enriched this image with new meanings. The article provides a literary analysis of several examples from English and Uzbek literature — Jack London’s “White Fang”, George Orwell’s “Animal Farm”, Cho‘lpon’s “Kecha va kunduz”, and representations of the dog image in contemporary Uzbek short fiction.